Research Progress of Physical Field Thawing on Foods - Yuhang WU; Yamei JIN; Xiao ZHANG; Huangbing YAO; Xueming XU; Na YANG (Shipin gongye ke-ji, 2024)
Freezing is an important method for food preservation, and some frozen foods still require separate thawing processes before consumption. Traditional thawing methods suffer from issues such as uneven temperature rise, long processing time, and significant loss of juices. As a new thawing technology, physical field thawing has received extensive research and attention in recent years. This paper reviews the research progress of physical field thawing in frozen food processing, and elaborates on the mechanisms and application effects of technologies such as ultrasound, dielectric, and electric fields in the thawing process. Compared to traditional thawing methods, physical field thawing better preserves the nutritional components of the ingredients, maintains sensory quality, reduces juice loss, and improves thawing efficiency. Different types of food materials and thawing methods may yield different effects, requiring analysis of the response characteristics and physicochemical parameters, such as dielectric constant, conductivity, and fat content, of actual ingredients to determine the optimal thawing conditions. Future research will focus on exploring efficient, stable, and low-energy physical field-assisted technologies, continuing in-depth studies on the impact on ingredient quality and thawing effects, to better meet consumers' demand for efficient processing of frozen foods.